The underworld : journeys to the depths of the ocean - Casey, Susan, 1962- (Doubleday, 2023)
"From New York Times bestselling author Susan Casey, an awe-inspiring portrait of the mysterious world beneath the waves, and the men and women who seek to uncover its secrets For all of human history, the deep ocean has been a source of wonder and terror, an unknown realm that evoked a singular, compelling question: What's down there? Unable to answer this for centuries, people believed the deep was a sinister realm of fiendish creatures and deadly peril. But now, cutting-edge technologies allow scientists and explorers to dive miles beneath the surface, and we are beginning to understand this strange and exotic underworld: A place of soaring mountains, smoldering volcanoes, and valleys 7,000 feet deeper than Everest is high, where tectonic plates collide and separate, and extraordinary life forms operate under different rules. Far from a dark void, the deep is a vibrant realm that's home to pink gelatinous predators and shimmering creatures a hundred feet long and ancient animals with glass skeletons and sharks that live for half a millennium-among countless other marvels. Susan Casey is our premiere chronicler of the aquatic world. For The Underworld she traversed the globe, joining scientists and explorers on dives to the deepest places on the planet, interviewing the marine geologists, marine biologists, and oceanographers who are searching for knowledge in this vast unseen realm. She takes us on a fascinating journey through the history of deep-sea exploration, from the myths and legends of the ancient world to storied shipwrecks we can now reach on the bottom, to the first intrepid bathysphere pilots, to the scientists who are just beginning to understand the mind-blowing complexity and ecological importance of the quadrillions of creatures who live in realms long thought to be devoid of life. Throughout this journey, she learned how vital the deep is to the future of the planet, and how urgent it is that we understand it in a time of increasing threats from climate change, industrial fishing, pollution, and the mining companies that are also exploring its depths. The Underworld is Susan Casey's most beautiful and thrilling book yet, a gorgeous evocation of the natural world and a powerful call to arms"--